Roles of retrovirus-derived PEG10 and PEG11/RTL1 in mammalian development and evolution and their involvement in human disease - Shiura, Hirosuke; Kitazawa, Moe; Ishino, Fumitoshi; Kaneko-Ishino, Tomoko (Frontiers in Cell and Developmental Biology, 2023)
PEG10 and PEG11/RTL1 are paternally expressed, imprinted genes that play essential roles in the current eutherian developmental system and are therefore associated with developmental abnormalities caused by aberrant genomic imprinting. They are also presumed to be retrovirus-derived genes with homology to the sushi-ichi retrotransposon GAG and POL, further expanding our comprehension of mammalian evolution via the domestication (exaptation) of retrovirus-derived acquired genes. In this manuscript, we review the importance of PEG10 and PEG11/RTL1 in genomic imprinting research via their functional roles in development and human disease, including neurodevelopmental disorders of genomic imprinting, Angelman, Kagami-Ogata and Temple syndromes, and the impact of newly inserted DNA on the emergence of newly imprinted regions. We also discuss their possible roles as ancestors of other retrovirus-derived RTL/SIRH genes that likewise play important roles in the current mammalian developmental system, such as in the placenta, brain and innate immune system.